The Influence Of Workload On Work Stress With Work-Family Conflict As Mediation In Employees Of The Badung Regency Health Office - Rizki Rahmadhani; I Gusti Made Suwandana (Al-Makki Publisher, 2025)
This study is motivated by the high work pressure experienced by employees in carrying out administrative tasks and health services, which triggers job stress and conflict between work and family roles At Dinas Kesehatan Kabupaten Badung. The purpose of this research is to examine the effect of workload on job stress with work-family conflict as a mediating variable among employees at the Badung District Health Office. This study employs a quantitative approach using path analysis with SPSS version 25. The sample consists of 73 civil servants selected through saturated sampling. Data were collected through an online questionnaire distributed via Google Forms, as well as preliminary observations and interviews to support initial understanding of the field phenomenon. The results show that workload has a positive and significant effect on job stress. Work-family conflict also has a positive and significant effect on job stress. Furthermore, work-family conflict partially mediates the relationship between workload and job stress. These findings support the Job Demands-Control Model, which suggests that high job demands without adequate control can increase job stress. Therefore, it is important for organizations to pay attention to workload distribution and to create a balance between job demands and employees' personal lives in order to reduce job stress levels.